Respostas fisiológicas e bioquímicas de plântulas de sorgo sob estresse salino e supridas com silício e fósforo - Ruppenthal, Viviane (2016)
The usage of silicon (Si) or phosphorus (P) as alleviators of the deleterious effects of salt stress has been reported to several crops, including sorghum. However, there is little information available about the effects of the combined application of both nutrients on physiological and biochemical, during seedling establishment of sorghum plants under salt stress. Thus, this research aimed to study the effects of combined Si and P supplementation in seedlings of two sorghum genotypes, CSF 18 and CSF 20, submitted to salinity. The experimental design was totally randomized, with four repetitions in a 2 x 2 x 2 factorial design,with the combination of two NaCl concentrations (0 and 100 mM), two silicon concentrations(0 and 0,5 mM) and two phosphorus concentrations (0 and 0,025 mM) as treatments. Si and P were applied to the culture media as sodium metasilicate (Na2SiO3) and monopotassium phosphate or monobasic potassium phosphate, KH2PO4), respectively. Sown was performed on germitest paper moistened with solutions of the respective treatments. 4 and 10 days after sowing (DAS), the growth parameters dry mass and length of roots and shoots were evaluateD, inorganic (Na+ and K+) and organic (water soluble carbohydrates, N – aminosolutes and proline)levels, water soluble protein content and the antioxidant activities of the enzymes superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX) and guaiacol peroxidase (GPX)in roots and shoots of seedlings of both sorghum genotypes were measured as well. Salinity affected negatively seedling growth in seedlings of both sorghum genotypes, except for 4 DAS seedlings, when root growth was favored with the addition of NaCl to the growth medium. The presence of Si and/or P in the growth medium did not alleviate the deleterious effects of salt stress on the growth variables here studied; however in non-stressed seedlings, those nutrients promoted a greater growth on both genotypes here studied. On the other hand, the addtition of NaCl into the nutrient solution inhibited the positive effects of P and S on growth of sorghum seedlings. Seedlings kept under salt stress, displayed an increase of Na+ levels in roots and shoots, while K+ levels in these parts either underwent an increase or remained unaltered, except for 10 DAS CSF 20 seedlings, which had a reduction on K+ levels in response to salinity. Si in growth media did not contribute to decrease Na+ absorption in sorghum plants submitted to salt stress; on the contrary, its addition promoted Na+ absorption. In general, for both genotypes, the organic solutes had its levels increased; however, they contributed little to alleviate the effects of salinity. Proline was the solute that had the highest accumulation of all. Nevertheless, Si and P addition induced a decrease in proline levels. Salinity generally increased the activities of the antioxidant enzymes here studied, however this increase did not confer higher tolerance to sorghum genotypes CSF 18 and CSF 20 to the damages caused by salt stress on growth. Si and/or P were not effective in the reduction of the damages caused by salt stress in sorghum genotypes CSF 18 and CSF 20 seedlings.